Surgical Site Infection caused by Non-Hemolytic Staphylococcus aureus Following a Total Knee Arthroplasty at a Class C Hospital in Indonesia - , Satiyo; Rosa, Elsye Maria (Folia Medica Indonesiana, 2023)
Highlights: • A patient with grade IV osteoarthritis underwent an arthroplasty and developed a surgical site infection caused by Staphylococcus aureus. • The treatment for the surgical site infection included antibiotic medications and revision surgery for the previous total knee arthroplasty. Abstract: This article presents a case report of a knee arthroplasty surgical site infection caused by non-hemolytic Staphylococcus aureus. A 56-year-old woman came to the Orthopedic Outpatient Clinic, with the chief complaint of pain in the left knee for the last three years. After being diagnosed with grade IV osteoarthritis, the patient underwent a total knee arthroplasty. The patient had routine post-operative follow-ups at the Orthopedic Outpatient Clinic. However, the patient complained of swelling, pain, and discharge at the surgical site after three months. The patient underwent a second surgery for debridement, implant removal, and interspacer placement. A broad-spectrum antibiotic (gentamicin) was administered while waiting for the culture and antibiotic sensitivity test results. The culture results showed non-hemolytic Staphylococcus aureus presence. The antibiotics were then changed and administered for two weeks according to the culture and antibiotic sensitivity test results. As the results were good, the patient was scheduled for revision surgery for her previous total knee arthroplasty.